Chemical Characterization of Extracted Ginger Oil Using GCMS - Shweta Chand,; Yogesh Kumar, (The Bioscan, 2025)
Aromatic plants are the species whose leaves, flowers, roots or other parts produce and release pleasant smells. Essential oils are plant extracts which are highly concentrated and are obtained from different parts of plants.Steam Distillation method is used to extract the essential oil of Ginger due to its quicker extraction time ,and simplicity of use. Mainly those compounds are separated from this method which are highly sensitive to the temperature. And component are observed after the analysis of GCMS(Gas Chromatography and Mass Spectrometry). After studying we found the component present in ginger are of mainly phenolic and tarpenoid compound. Eugenol is one of the compound which is found as phenolic and Endo Borneol as tarpenoid compound .While having the analysis we found 10 compounds are observed as major in which Eugenol having a percentage of 78.81.